Numerical Analysis of Reinforced Concrete Circular Columns Strengthening With CFRP under Concentric and Eccentric Loadings (Fracture and Structural Integrity, 2022)
The purpose of this study is to explore the numerical behavior of circular RC short columns with different degrees of confinement with CFRP (0%, 25%, 50%, and 100%) wraps under concentric and eccentric loading. The numerical analysis carried out by using an improved concrete plastic-damage model (CDPM) implemented in ABAQUS software for finite element (FE) analysis. The FE model simulated a total of twenty-four numerical specimens. The findings were matched to published experimental test results in the literature. The findings of the FE model and the experimental data were good similar. As a consequence, the model was found to be valid. The numerical results shows that as load eccentricity increased, the load carrying capacity of columns decreased for unconfined specimens, whereas the decline in strength for confined specimens becomes limited as the degrees of confinement ratio increased. In addition, increasing the CFRP confinement ratio improves the column's load-bearing capability at the same load eccentricity.
Keywords: short circular column; numerical analysis; plastic-damage model; CFRP; eccentric load; ABAQUS software